Factors Influencing Smallholder Bean Producer’s Participation in Collective Marketing in Kawambwa, Luwingu and Senga Hill Districts of Zambia - Chikuta, Trevor; Sichoongwe, Kiru; Nakanga, Austine (International Journal on Food, Agriculture and Natural Resources, 2024)
Commercialization of agricultural produce through cooperatives that undertake collective marketing can decrease transactions costs for smallholder farmers. This study investigated the factors influencing smallholder bean producers’ decision to participate and intensity of participation in collective marketing in Kawambwa, Luwingu and Senga Hill districts of Zambia. A multi-stage sampling design was used to draw 150 smallholder farmers from cooperatives from the three districts. Cross sectional data were collected through semi structured questionnaire and in-depth focused group discussions were also conducted with the three cooperatives. Double hurdle results revealed that the decision to participate in collective marketing was influenced by age, gender, household size, farm size, output price, farm income, hybrid seed, access to market information, ownership of a bicycle, radio and mobile phone. On the other hand, the determinants of intensity of participation in collective marketing were education level of the household head, bean output and distance to the nearest market. To increase smallholder farmers’ participation in collective marketing, there is need to focus on policies that enhance access to market information, promotion and adoption of hybrid bean varieties, increased bean production and construction of bulking facilities in rural areas away from main markets. Smallholder farmers who have attained at least primary level education should be targeted as well as encourage youth and women participation.